Communication strategies in management: a case study of interpersonal manager-staff communication at a South African university - Balarin, Megan Georgina (Rhodes University, Faculty of Education, Department of Education, 2006)
Communication is a central feature of human life. The ability to talk is the very feature that distinguishes us from our primate ancestors. Knowing how to use language effectively gives the bearers of this knowledge power over their environment and an upper hand in their dealings with others. Thus, understanding the importance of communication in management is an essential tool for managers who wish to build and develop their organisations and their staff within these organisations. This thesis takes a case study view of manager-staff communication at a South African university. In this study managers and staff members contribute their feelings on current communication practices at this organisation through an online questionnaire and in-depth interviews. In an interpretive paradigm this thesis answers three central questions: 1) what role do managers and staff think communication plays in their working relationships, 2) what do they perceive to be effective and ineffective communication strategies and 3) What strategies can they suggest to enhance effective communication? Through in-depth qualitative research and numerical data analysis this thesis discovers central themes that pertain to the effective flow of communication in this organisation. These themes include: motivation and praise, the role of listening, building relationships, respect, acknowledging others' languages and cultures, building teams, communicating frequently and using email and technology effectively, as well as keeping notes of meetings and discussions. Challenges to effective communication include not having enough time, suffering from stress, and the challenges of physical space and distance. By paying attention to basic human principles, such as the fact that acknowledging people for a job well done encourages them to perform well in future, this thesis relates the general concepts of communication and management theory to the specific realities and individual, personal experiences of manager-staff communication. In this way it sheds a beam of light on management communication practices and points the way towards an ideal where managers and staff members use communication as a tool of empowerment and understanding.
Keywords: Communication in management -- South Africa; Interpersonal communication -- South Africa; Communication -- Education; College personnel management -- South Africa; Universities and colleges -- South Africa; Education, Higher -- South Africa -- Management